การผลิตเยื่อจากกากมันสำปะหลังที่ผ่านการขจัดแป้งสำหรับการผลิตกระดาษแข็งประกบลูกฟูก - ธิดารัตน์ กาญจนธนาเลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Cassava residue is a waste from starch industry which contains considerable amount of cellulose and hemicellulose. It could be mixed with pulps as a substitution for wood-based fibers and turned into value-added products. This research aimed to find the suitable method for pulping starch-removed cassava residue, as starch interferes with the ability of fibers to form the sheet, for linerboard production. Cassava residue was screened and starch-extracted by alpha-amylase for acid, neutral and alkaline pulping. It was found that alkaline pulping produced pulp with highest quality. In order to find optimum pulping conditions, starch-removed cassava residue was again soda pulped using conditions which varied in cooking temperature, time and NaOH concentration. These pulps were then blended with hardwood pulp at the ratio of 10:90 w/w and made into handsheets. It was found that the optimum pulping condition is with 18% NaOH at 100°C for 120 minutes where it gave best tensile strength. The pulp from the optimum condition was then compared with cassava residue mechanically pulped by beating to the freeness of 350±30 milliliters and 244±6 milliliters, by blending with Old Corrugated Container (OCC) pulp at the ratio of 10:90. It was found that soda pulping of cassava residues could reduce shives which was the major problem of this research, better than mechanical pulping. In addition, it gave better physical properties. Print density of sheets from chemical pulp was found to be similar to that of mechanical pulp.